KOMPARASI MODEL PEMBELAJARAN PORTOFOLIO DAN PBL TERHADAP HASIL BELAJAR PAI DI SMPS YAYASAN PERGURUAN UTAMA DAN YAYASAN HAMDI HUSNI KECAMATAN MEDAN TEMBUNG - SODRI; ABDILLAH (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
This study aims to find out: (1) the differences of learning outcomes between students who learn by using portfolio learning models and PBL learning models; (2) the difference of the learning outcome between the use of portfolio learning models and PBL learning models at learners who have high learning motivation ; (3) the difference of the learning outcome between the use of portfolio learning models and PBL learning models at learners who have low learning motivation; and (4) the interaction effect between of learning models and students motivation to learning outcomes. This was a quasi experiment research study employing the factorial 2x2 design. The data analysis used the varian analyzes (Anava) two way with significance level of (α) 0.05. The results of the research show that: (1) There are significant differences in learning outcomes between students who learn by using using portfolio learning models and PBL learning models; (2) There are significant differences in learning outcomes between the use of portfolio learning models and PBL learning models at learners who have high learning motivation; (3) there are significant differences of the learning outcome between the use of portfolio learning models and PBL learning models at learners who have low learning motivation; and (4) There are significant interaction effect between of learning models and students motivation to learning outcomes